The Impact of the Online Project-Based Learning on Students’ Communication, Engagement, Motivation, and Academic Achievement - Ханса Хассан Аль-Бахадлі; Лікаа Хабеб Аль-Обайді; Марсель Пікхарт (Психолінгвістика, 2023)
Purpose. Project-based learning (PBL) is a student-centered environment that emphasizes a dynamic classroom approach. It is founded on the idea that students gain a deeper understanding by actively tackling difficulties and issues from the real world. Students gain knowledge in a subject by devoting a significant amount of time to researching and solving a challenging question or interesting issue.